The Implementation of Formative Assessment and Student Self-Reflection in English Writing Performance - Syahmiarni Syahmiarni; Devi Triana; Immatul Jannah Alimir; Arifmiboy Arifmiboy; Absharini Kardena (English Department - University of Sultan Ageng Tirtayasa, 2026)
This study investigates how formative assessment and student self-reflection contribute to improving secondary EFL learners’ performance in writing procedure texts. Although procedure text has a clear generic structure—goal, materials, and sequenced steps—previous studies show that students often struggle with organizing instructions, using accurate imperative verbs, and maintaining logical coherence. To explore how instructional practices can address these challenges, this research employed a descriptive qualitative design involving a Grade 9 class at SMP Islam Al-Ishlah Bukittinggi. Data were collected through classroom observations, document analysis of students’ writing work, and semi-structured interviews with both the teacher and students. The findings indicate that formative assessment, delivered through written comments, oral clarification, modeling, and peer-review, provided continuous guidance has helped students identify and revise structural and linguistic weaknesses in their texts. Meanwhile, self-reflection enabled learners to evaluate their work more critically, internalize teacher feedback, and plan revisions more purposefully. Evidence from the writing work shows improvement in sequencing, verb accuracy, clarity of instructions, and completeness of materials. The study concludes that integrating formative assessment with reflective practices creates a mutually reinforcing writing environment that enhances genre awareness, metacognitive engagement, and overall writing quality.